The Gentle Puritan : A Life of Ezra Stiles, 1727-1795 - Morgan, Edmund S. (Edmund Sears), 1916-2013 (Book collections on Project MUSE., 2015)
Now available again, this important biography of the early New England intellectual leader was greeted as a "landmark in the history of the American mind" by Clifford K. Shipton when it appeared in 1962. Stiles lived at a critical time--the transition from the Reformation to the Enlightenment, which came suddenly in New England--and because of his position, his influence was great."